The influence of ABO blood groups on sensitization of potential kidney transplant recipients - Hassan, Ahmed; Sherif, Mohamed; Khalil, Rasha; Zaki, Medhat (African Journal of Nephrology, 2016)
<div style="text-align: left; color: #000000; font-family: 'Merrieweather sans', sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;"> In this study 50 chronic renal failurepatients were tested for blood ABO groups and forthe presence of lymphocytotoxic antibodies against apanel of 20 donor lymphocytes (of known HLAtypes) using microcytotoxicity assay. The influenceof other factors affecting sensitization, such asnumber of blood transfusions, pregnancies andprevious graft rejections were analyzed too. Theresults showed that41.2 % of blood group 0 patients,61.1 % of group A I, 90% of group B, and 80% ofgroup A IB are sensitized (PRA> 10%).These results pointed to higher incidence ofsensitization in patients with blood groups B andA IB as compared to groups A I and 0.Our data suggest an impact of the ABO system on thesensitization phenomenon.